Cost-effectiveness of increased screening and treatment of chronic hepatitis C in Korea. (2nd June 2020) - Kim, Do Young; Wong, Gabriel; Lee, Janet; Kim, Myung Hwa; Smith, Nathaniel; Blissett, Rob; Kim, Hyung Joon
Abstract: Background: Given a hepatitis C virus (HCV) elimination goal by 2030, World Health Organization (WHO) guidelines recommend scaling up HCV screening and treatment with highly-effective direct-acting antivirals (DAAs). This study investigated the cost-effectiveness of various screening and treatment strategies for chronic HCV patients in South Korea in patients aged over 40 as compared to currently screening only high-risk patients. Methods: A published Markov disease progression model was used with a screening/treatment decision-tree to model different screening and treatment strategies for Korean HCV patients (aged over 40) from a national payer perspective over a lifetime time horizon. The screening strategies included "screen-all" (upfront only: "once"; or upfront and age 65: "twice") or a "high-risk only" screening strategy followed by treatment. Treatment strategies included either ledipasvir/sofosbuvir (LDV/SOF), SOF + ribavirin (SOF + RBV; in GT2 only), or glecaprevir/pibrentasvir (GLE/PIB). Model inputs were sourced from published literature and costing databases and validated by Korean hepatologists. Results: Regardless of treatment strategy, a "screen all twice" scenario led to the lowest rates of advanced liver disease events compared to "screen all once" and "high-risk only" screening scenarios. In this screening scenario, treatment with LDV/SOF for GT1/2 dominates (i.e. is more effective and less4costly) LDV/SOF in GT1 and SOF + RBV in GT2, while GLE/PIB is not cost-effective relative to LDV/SOF (₩105, 124, 920/QALY) at a willingness-to-pay threshold of 1xGDP per capita. Conclusion: Screening all South Korean patients twice followed by LDV/SOF treatment is cost-effective as compared current high-risk screening. Adopting this strategy can help achieve WHO HCV elimination goals.